Graphene nonwoven fabric / polyurethane conductive composite material, preparation method and application

By changing the swelling parameters and high-temperature reduction treatment, the crosslinking degree of graphene non-woven fabric is controlled and combined with polyurethane, the problem of unstable strain conductivity in flexible sensors is solved, and a wider application is achieved .

CN116556076BActive Publication Date: 2025-02-11UNIV OF SCI & TECH BEIJING
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310442144.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-04-23
Publication Date
2025-02-11
Estimated Expiration
2043-04-23

AI Technical Summary

Technical Problem

The existing graphene non-woven fabrics are unstable in flexible sensors, and the degree of connection between fibers is uncontrollable, resulting in large differences in conductivity and unstable mechanical properties, which limits its improvement in the field of flexible conductive composite materials. Widely used.

Method used

By changing the swelling ratio and time of water and alcohol, a graphene oxide non-woven fabric structure with different crosslinking degrees is formed, and after high-temperature reduction, it is composited with polyurethane to prepare a highly flexible graphene non-woven fabric/TPU composite material.

Benefits of technology

The control of the overlap between fibers inside graphene non-woven fabrics is achieved, and materials with different strain conductivity are prepared, which broadens the application of graphene non-woven fabrics in the field of flexible conductive composite materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116556076B_ABST
    Figure CN116556076B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of application of conductive composite materials in sensors, and provides a graphene non-woven fabric / polyurethane conductive composite material, a preparation method and an application. The preparation method comprises: preparing graphene oxide fibers by wet spinning, regulating the structure of the graphene non-woven fabric by different swelling ratios, and filling and curing the polyurethane. The composite material is composed of a conductive graphene non-woven fabric and a thermoplastic polyurethane substrate. The graphene non-woven fabrics prepared by different swelling ratios in the composite material exhibit different morphological structures, and after being compounded with polyurethane, a good combination of polyurethane and graphene non-woven fabrics of different structures is achieved; the present invention provides a simple and quick structural design method for the in-depth research and application of graphene non-woven fabrics.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of application of conductive composite materials in sensors, and in particular to a graphene non-woven fabric / polyurethane conductive composite material, a preparation method and application thereof. Background Art

[0002] With the continuous development of flexible wearable electronic devices, flexible conductive composite materials with low density, high conductivity and excellent tensile and bending properties have been widely studied. Compared with traditional metal conductive materials, emerging carbon materials such as graphene, carbon nanotubes and carbon nanofibers have attracted great attention due to their advantages of light weight, good conductivity and high flexibility after composite curing with polymers such as polydimethylsiloxane (PDMS) and polyurethane (TPU). Among them, graphene, as a new type of two-dimensional material, has attracted a lot of attention due to its excellent electrical and thermal conductivity and high strength and high modulus properties. In recent years, in particular, the method of preparing graphene fibers from graphene oxide solution through wet spinning process has aroused the interest of many scientific researchers, and has extended to many research directions such as graphene fiber fabrics, graphene fiber non-woven fabrics and graphene fiber aerogels, greatly enriching the practical application of graphene.

[0003] The graphene oxide non-woven fabric prepared by wet spinning technology has a large number of oxygen-containing functional groups on its surface, which makes it very easy to achieve fiber grafting modification or overall appearance structure construction; the graphene non-woven fabric made by high-temperature reduction has the characteristics of high conductivity, high thermal conductivity, and high porosity, which makes it attract much attention in many new energy device research fields, especially in the field of flexible strain sensing. At present, the application of pure carbon materials in the field of flexible sensors is limited to a certain extent due to the brittleness of carbon materials themselves and poor strain conductivity. The graphene oxide non-woven fabric prepared by air spinning or short fiber filtration has a rich multi-dimensional structure that can improve the strain sensing performance of carbon materials in flexible sensors within a certain range. However, the uncontrollable degree of connection between its fibers causes large differences in conductivity and unstable mechanical properties in the strain sensor under a large strain range, which limits the wider research and application of graphene non-woven fabrics in the field of flexible conductive composite materials to a certain extent.

[0004] Therefore, the technical problem solved by the present invention is to explore new experimental preparation parameters to control the overlap degree between fibers inside the graphene non-woven fabric, thereby preparing graphene non-woven fabrics with different strain conductivity properties, and further broaden the application of graphene non-woven fabrics in the field of flexible conductive composite materials. Summary of the invention

[0005] The purpose of the present invention is to provide a graphene non-woven fabric / polyurethane conductive composite material, a preparation method and an application thereof on the basis of the prior art. After the long graphene oxide fibers are interrupted, the swelling ratio and time of water and alcohol are changed to form graphene oxide non-woven fabric structures with different cross-linking degrees, and then the graphene oxide non-woven fabric structures are compounded with polymers after high-temperature reduction to form a highly flexible graphene non-woven fabric / TPU composite material.

[0006] The present invention adopts the following technical solution:

[0007] In one aspect, the present invention provides a method for preparing a graphene non-woven fabric / polyurethane conductive composite material, comprising:

[0008] S1. Preparing graphene oxide fibers by wet spinning;

[0009] S2, weighing, homogenizing, breaking, swelling and vacuum filtering the graphene oxide fibers obtained in step S1 to obtain a graphene oxide non-woven fabric;

[0010] S3, chemically reducing the graphene oxide non-woven fabric obtained in step S2 with hydroiodic acid and performing high-temperature reduction to obtain a graphene non-woven fabric;

[0011] S4, cutting, coating with a polyurethane solution, and curing the graphene non-woven fabric obtained in step S3 to obtain a graphene non-woven fabric / polyurethane conductive composite material.

[0012] Any possible implementation as described above further provides an implementation, in step S1, the diameter of the needle used to prepare the graphene oxide fiber is 0.13 mm, 0.18 mm or 0.25 mm.

[0013] Any possible implementation as described above further provides an implementation, in which in step S2, the weight of the graphene oxide fiber is between 0.02-0.1 g.

[0014] Any possible implementation as described above further provides an implementation, in step S2, the solution swells, and the graphene oxide non-woven fabric is swelled using three swelling parameters of alcohol to water volume ratio of 4:1, 1:1, and 1:4.

[0015] Any possible implementation as described above further provides an implementation, in step S3, the prepared graphene oxide non-woven fabric is reduced using hydroiodic acid / acetic acid at 90° C. for 12 hours, and then reduced at 1600° C. for 40 minutes to obtain the graphene non-woven fabric.

[0016] Any possible implementation as described above further provides an implementation, in step S4, the reduced graphene non-woven fabric is cut into a width of 0.5 cm, 1 cm, 1.5 cm or 2 cm, placed in a mold, coated with a polyurethane solution, and cured.

[0017] Any possible implementation as described above further provides an implementation, in which in step S4, when compounding the polyurethane substrate, the film thickness is controlled by adjusting the amount of the polyurethane solution.

[0018] On the other hand, the present invention also provides a graphene non-woven fabric / polyurethane conductive composite material, which is prepared using the above-mentioned preparation method.

[0019] Any possible implementation as described above further provides an implementation in which, under a tensile strain of 40%,

[0020] When the volume ratio of alcohol to water is 4:1, the GF of the graphene nonwoven fabric prepared by swelling reaches 100;

[0021] When the volume ratio of alcohol to water is 1:1, the GF of the graphene nonwoven fabric prepared by swelling is 25;

[0022] When the volume ratio of alcohol to water is 1:4, the GF of the graphene nonwoven fabric prepared by swelling is 9.5.

[0023] Where GF is the strain sensitivity factor, which is equal to (resistance change ΔR / initial resistance value R0) / strain, that is, Where R is the resistance and L is the sensor length.

[0024] On the other hand, the present invention also provides a graphene non-woven fabric / polyurethane strain sensor, which uses the above-mentioned graphene non-woven fabric / polyurethane conductive composite material; the preparation method of the strain sensor is: cutting the prepared graphene fiber non-woven fabric into rectangular blocks, gluing copper wires at both ends with conductive silver glue and placing it in a polytetrafluoroethylene sample plate, taking it out after drying and pouring the configured polyurethane TPU solution, vacuum defoaming and drying, and then obtaining the graphene non-woven fabric / polyurethane strain sensor.

[0025] The beneficial effects of the present invention are:

[0026] Compared with the prior art, the present invention conveniently and quickly prepares graphene non-woven fabrics with different swelling degrees by changing the experimental parameters in the swelling process, and provides a large number of experimental parameters for the subsequent construction of different non-woven fabric structures to achieve different experimental effects by characterizing the influence of the morphology and structure on the tensile conductive properties, thereby further broadening the application of graphene non-woven fabrics in the fields of battery negative electrode materials, flexible wearable devices, etc. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 Shown is a schematic flow chart of a method for preparing a graphene non-woven fabric / polyurethane conductive composite material according to an embodiment of the present invention.

[0028] Figure 2 Shown are the morphological structures of the graphene fiber nonwoven fabric in the embodiment after swelling and reduction in alcohol / water at a ratio of 4:1, 1:1, and 1:4; (a) 4:1; (b) 1:1; (c) 1:4.

[0029] Figure 3 Shown is a real picture of the graphene nonwoven fabric / TPU composite material stretched in the embodiment: a is 0% strain; b is 40% strain.

[0030] Figure 4 Shown is the tensile strain resistance change curve of the graphene non-woven fabric / TPU composite material in the embodiment. DETAILED DESCRIPTION

[0031] The specific embodiments of the present invention will be described in detail below in conjunction with specific drawings. It should be noted that the technical features or combinations of technical features described in the following embodiments should not be considered isolated, and they can be combined with each other to achieve better technical effects.

[0032] like Figure 1 As shown in the preparation flow chart, a method for preparing a graphene non-woven fabric / polyurethane conductive composite material according to an embodiment of the present invention comprises:

[0033] S1. Preparing graphene oxide fibers by wet spinning;

[0034] S2, the graphene oxide fibers obtained in step S1 are broken by homogenization, swelled by solution, and vacuum filtered to obtain a graphene oxide non-woven fabric;

[0035] S3, chemically reducing the graphene oxide non-woven fabric obtained in step S2 with hydroiodic acid and performing high-temperature reduction to obtain a graphene non-woven fabric;

[0036] S4, coating the graphene non-woven fabric obtained in step S3 with a polyurethane solution, and curing the solution to obtain a graphene non-woven fabric / polyurethane conductive composite material.

[0037] In a specific embodiment, in step S1, the needle diameter for preparing the graphene oxide fiber is 0.13mm, 0.18mm or 0.25mm. The graphene oxide fiber prepared using the above three needle inner diameter sizes, after drying and reduction, the diameter of the fiber is greatly reduced, and the fiber diameter is not equal to the needle diameter. From the characteristics of the material itself, the Young's modulus of the same material itself is basically unrelated to the diameter length, but the Young's modulus of the graphene fiber of different diameters prepared by graphene oxide has also changed. The reason is that when the same size graphene oxide / DMF solution is used to prepare graphene oxide fiber, due to the difference in the inner diameter of the needle, different shear forces are produced on the graphene oxide lamellae, so the stacking mode of the graphene oxide lamellae inside the graphene oxide fiber prepared has changed, which is macroscopically manifested as the mechanical properties of the graphene fiber changing, and the fiber Young's modulus prepared when the needle diameter is 0.18mm is the highest.

[0038] In a specific embodiment, in step S2, the weight of the graphene oxide fiber is between 0.02-0.1 g.

[0039] In a specific embodiment, in step S2, the solution is swelled, and the graphene oxide non-woven fabric is swelled using three swelling parameters of alcohol to water volume ratio of 4:1, 1:1, and 1:4.

[0040] In a specific embodiment, in step S3, the prepared graphene oxide non-woven fabric is reduced using hydroiodic acid / acetic acid at 90° C. for 12 hours and then reduced at 1600° C. for 40 minutes to obtain the graphene non-woven fabric.

[0041] In a specific embodiment, in step S4, the reduced graphene non-woven fabric is cut into a width of 0.5 cm, 1 cm, 1.5 cm or 2 cm, placed in a mold, coated with a polyurethane solution, and cured; when composited with a polyurethane substrate, the film thickness is controlled by adjusting the amount of the polyurethane solution.

[0042] The embodiment of the present invention is a graphene non-woven fabric / polyurethane strain sensor. The prepared graphene fiber non-woven fabric is cut into rectangular blocks, copper wires are glued to both ends with conductive silver glue, and then placed in a polytetrafluoroethylene sample plate. After drying, it is taken out and poured into a prepared polyurethane TPU solution, and then dried after vacuum defoaming to obtain a graphene non-woven fabric / polyurethane strain sensor.

[0043] Example 1

[0044] A method for preparing a graphene non-woven fabric / polyurethane conductive composite material, comprising:

[0045] (1) centrifuging the graphene oxide aqueous dispersion at 8000 rpm to replace water in the solution with dimethylformamide (DMF) to form a graphene oxide / DMF dispersion with a concentration of 8 g / ml;

[0046] (2) by wet spinning, at a pushing speed of 0.08 mm / min, the graphene oxide / DMF dispersion was squeezed into an ethyl acetate coagulation bath through a needle to coagulate and form, and after being pulled, it was dried at 50° C.; after being drawn by a guide roller, the fiber was stretched to a certain extent, and was wound and collected at a winding speed of 1.8 rpm to prepare graphene oxide long fibers;

[0047] (3) The prepared graphene oxide fibers were dried at 30°C for 12 h and then at 70°C for 3 h, then placed in ethyl acetate and immediately broken into short fibers with uniform length distribution using a homogenizer at 10,000 rpm. After filtering, they were poured into an alcohol / water solution mixed in a 4:1 volume ratio, swelled for 1 min, and then vacuum filtered. The graphene oxide non-woven fabric obtained after filtration was dried and reduced at high temperature to obtain a graphene fiber non-woven fabric. The graphene fiber diameter is between 20-50 μm, there are a large number of wrinkles on the fiber surface, and there is a small amount of overlap between the fibers. After swelling and drying, the fibers have obvious expansion, see for details. Figure 2 Middle (a);

[0048] (4) The prepared graphene fiber non-woven fabrics with different cross-linking degrees were cut into 10x30 mm rectangles, and copper wires were glued to both ends with conductive silver glue and placed in a polytetrafluoroethylene sample plate. After drying at 60 °C for 10 min, the prepared TPU solution was taken out and poured into the plate. After vacuum defoaming, the solution was dried at 45 °C for 10 h. The actual graphene non-woven fabric / TPU sensor after drying is shown in the figure below. Figure 3 As shown in (a);

[0049] The graphene nonwoven fabric / TPU composite material obtained above was placed in a fixture, and a tensile machine-digital source meter combination was used to measure the resistance change of the material under extreme tensile fracture at a speed of 12mm / min. The test found that when the tensile strain reached 50%, the resistance change rate reached 10000%. Under this strain, the internal structure of the nonwoven fabric was destroyed and could not be connected to each other to form a good conductive network, resulting in a high resistance change rate with strain. For details, see Figure 4 .

[0050] Example 2

[0051] A method for preparing a graphene non-woven fabric / polyurethane conductive composite material, comprising:

[0052] (1) centrifuging the graphene oxide aqueous dispersion at 8000 rpm to replace water in the solution with dimethylformamide (DMF) to form a graphene oxide / DMF dispersion with a concentration of 8 g / ml;

[0053] (2) by a wet spinning method, at a pushing speed of 0.08 mm / min, the graphene oxide solution was squeezed into an ethyl acetate coagulation bath through a needle to coagulate and form, after being pulled, dried at 50° C., the fiber was stretched to a certain extent after being drawn by a guide roller, and then wound and collected at a winding speed of 1.8 rpm to prepare graphene oxide long fibers;

[0054] (3) Dry the prepared graphene oxide fiber at 30°C for 12 hours and then at 70°C for 3 hours, then put it into ethyl acetate and immediately break it into short fibers with uniform length distribution using a homogenizer at 10,000 rpm, filter it and pour it into a prepared 1:1 volume ratio alcohol / water solution, swell it for 1 minute and then vacuum filter it. The graphene oxide non-woven fabric obtained after filtration is dried and reduced at high temperature to obtain a graphene fiber non-woven fabric; Figure 2 In (b), the fiber diameter is between 30-70 μm. The increase in water content increases the fiber swelling degree, increases the degree of cross-linking between fibers, and changes the overall morphology of the nonwoven fabric. For details, see Figure 2 (b)

[0055] (4) The prepared graphene fiber non-woven fabrics with different cross-linking degrees were cut into rectangles of 10x30 mm, copper wires were glued to both ends with conductive silver glue, and then placed in a polytetrafluoroethylene sample plate. After drying at 60°C for 10 min, the prepared TPU solution was taken out and poured into the plate. After vacuum defoaming, the plate was dried at 45°C for 10 h.

[0056] The graphene nonwoven fabric / TPU composite material obtained above was placed in a fixture, and a tensile testing machine-digital source meter combination was used to measure the resistance change of the material under ultimate tensile fracture at a speed of 12 mm / min. Figure 4 The analysis shows that the fiber strain is significantly increased, the linearity of the tensile strain / resistance change rate is significantly improved, and a good linearity can still be maintained at 70% strain.

[0057] Example 3

[0058] A method for preparing a graphene non-woven fabric / polyurethane conductive composite material, comprising:

[0059] (1) centrifuging the graphene oxide aqueous dispersion at 8000 rpm to replace water in the solution with dimethylformamide (DMF) to form a graphene oxide / DMF dispersion with a concentration of 8 g / ml;

[0060] (2) by a wet spinning method, at a pushing speed of 0.08 mm / min, the graphene oxide solution was squeezed into an ethyl acetate coagulation bath through a needle to coagulate and form, after being pulled, dried at 50° C., the fiber was stretched to a certain extent after being drawn by a guide roller, and then wound and collected at a winding speed of 1.8 rpm to prepare graphene oxide long fibers;

[0061] (3) Dry the prepared graphene oxide fiber at 30°C for 12 hours and then at 70°C for 3 hours, then put it into ethyl acetate and immediately break it into short fibers with uniform length distribution using a homogenizer at 10,000 rpm, filter it and pour it into a prepared alcohol / water solution mixed in a volume ratio of 1:4, swell for 1 minute and then vacuum filter it. The graphene oxide non-woven fabric obtained after filtration is dried and reduced at high temperature to obtain a graphene fiber non-woven fabric; Figure 2 (c) Analysis shows that the fiber diameter is distributed in the range of 50-120 μm, the fibers swell significantly, the cross-links between the fibers are in the form of a film, the fibers are more closely overlapped, and the nonwoven fabric morphology and structure are more compact;

[0062] (4) The prepared graphene fiber non-woven fabrics with different cross-linking degrees were cut into rectangles of 10x30 mm, copper wires were glued to both ends with conductive silver glue, and then placed in a polytetrafluoroethylene sample plate. After drying at 60°C for 10 min, the prepared TPU solution was taken out and poured into the plate. After vacuum defoaming, the plate was dried at 45°C for 10 h.

[0063] The graphene nonwoven fabric / TPU composite material obtained above was placed in a fixture, and a tensile testing machine-digital source meter combination was used to measure the resistance change of the material under ultimate tensile fracture at a speed of 12 mm / min. Figure 4 It can be analyzed that the highly cross-linked graphene non-woven fabric has a larger tensile strain, a resistance change rate of 2000% under 80% strain and good linearity.

[0064] Example 4

[0065] A method for preparing a graphene non-woven fabric / polyurethane conductive composite material, comprising:

[0066] (1) centrifuging the graphene oxide aqueous dispersion at a high speed of 10,000 rpm to replace the water in the solution with dimethylformamide (DMF) to form a graphene oxide / DMF dispersion with a concentration of 10 g / ml;

[0067] (2) by a wet spinning method, at a pushing speed of 0.08 mm / min, the graphene oxide solution was squeezed into an ethyl acetate coagulation bath through a needle to coagulate and form, after being pulled, dried at 50° C., the fiber was stretched to a certain extent after being drawn by a guide roller, and then wound and collected at a winding speed of 1.8 rpm to prepare graphene oxide long fibers;

[0068] (3) Dry the prepared graphene oxide fiber at 30°C for 12 hours and then at 70°C for 3 hours, then put it into ethyl acetate and immediately break it into short fibers with uniform length distribution using a homogenizer at 10,000 rpm, filter it and pour it into a prepared 1:1 volume ratio alcohol / water solution, swell it for 1 minute and then vacuum filter it. The graphene oxide non-woven fabric obtained after filtration is dried and reduced at high temperature to obtain a graphene fiber non-woven fabric;

[0069] (4) The prepared graphene fiber non-woven fabrics with different cross-linking degrees were cut into rectangles of 10x30 mm, copper wires were glued to both ends with conductive silver glue, and then placed in a polytetrafluoroethylene sample plate. After drying at 60°C for 10 min, the prepared TPU solution was taken out and poured into the plate. After vacuum defoaming, the plate was dried at 45°C for 10 h.

[0070] The graphene nonwoven fabric / TPU composite material obtained above was placed in a fixture, and a tensile machine-digital source meter combination was used to measure the resistance change of the material under ultimate tensile fracture at a speed of 12 mm / min. Example 4 changes the centrifugal speed and increases the concentration of the graphene oxide dispersion. The mechanical properties of the fiber prepared from the high-concentration graphene dispersion will change, and thus the mechanical properties of the prepared fiber membrane will also be affected.

[0071] Example 5

[0072] A method for preparing a graphene non-woven fabric / polyurethane conductive composite material, comprising:

[0073] (1) centrifuging the graphene oxide aqueous dispersion at 8000 rpm to replace water in the solution with dimethylformamide (DMF) to form a graphene oxide / DMF dispersion with a concentration of 8 g / ml;

[0074] (2) by a wet spinning method, at a pushing speed of 0.25 mm / min, the graphene oxide solution is squeezed into an ethyl acetate coagulation bath through a needle to coagulate and form, after being pulled, dried at 50° C., the fiber is stretched to a certain extent after being drawn by a guide roller, and then wound and collected at a winding speed of 8 rpm to prepare graphene oxide long fibers;

[0075] (3) Dry the prepared graphene oxide fiber at 30°C for 12 hours and then at 70°C for 3 hours, then put it into ethyl acetate and immediately break it into short fibers with uniform length distribution using a homogenizer at 10,000 rpm, filter it and pour it into a prepared 1:1 volume ratio alcohol / water solution, swell it for 1 minute and then vacuum filter it. The graphene oxide non-woven fabric obtained after filtration is dried and reduced at high temperature to obtain a graphene fiber non-woven fabric;

[0076] (4) The prepared graphene fiber non-woven fabrics with different cross-linking degrees were cut into rectangles of 10x30 mm, copper wires were glued to both ends with conductive silver glue, and then placed in a polytetrafluoroethylene sample plate. After drying at 60°C for 10 min, the prepared TPU solution was taken out and poured into the plate. After vacuum defoaming, the plate was dried at 45°C for 10 h.

[0077] The graphene nonwoven fabric / TPU composite material obtained above is placed in a fixture, and a tensile machine-digital source meter combination is used to measure the resistance change of the material under ultimate tensile fracture at a speed of 12 mm / min. Example 5 The spinning push speed is changed. The faster push speed changes the morphology of the spun graphene fiber. The stacking mode between the graphene sheets changes the shear force inside the needle due to the increase in the push speed, and then the prepared graphene morphology structure changes, which ultimately affects the mechanical properties of the graphene fiber.

[0078] The inventors found in a large number of experiments that the swelling effect of graphene oxide non-woven fabrics will become stronger and stronger with the increase of water ratio, and the strain conductivity (GF) of the sensor after being made will gradually weaken with the enhancement of the swelling effect. When pure alcohol is used or the alcohol ratio is greater than 4, the mechanical properties of the non-woven fabric are poor, and the strain range of the sensor after being made is too low to be applied. When the water ratio is greater than 4, the sensor has a better strain range, but its overall GF is too low, making it difficult to use in micro-strain application environments, and the sensors made of graphene non-woven fabrics prepared with different swelling parameters have low differences, and the overall performance difference is not large, so it is not desirable.

[0079] Among the several parameters between the alcohol-to-water ratio of 4:1 and 1:4, the alcohol-to-water ratio of 1:1 is the optimal value in the middle, that is, it has both a higher strain range and better sensitivity, which can meet multiple application scenarios. The other swelling parameters (such as alcohol-to-water ratios of 3:1, 2:1, 1:2, and 1:3) either have a smaller strain range than the 1:1 parameter or a lower sensitivity than the 1:1 parameter. Overall, the three groups of parameters of 4:1, 1:1, and 1:4 are the optimal parameter choices.

[0080] In the above embodiments of the present invention, graphene nonwoven fabrics prepared with different swelling ratios exhibit different morphological structures. After being compounded with polyurethane, a good combination of polyurethane and graphene nonwoven fabrics with different structures is achieved. Under 40% tensile strain, the GF of the graphene nonwoven fabric prepared by swelling with an alcohol ratio of water (4:1) is as high as 100, while the GF of the graphene nonwoven fabric prepared by swelling with an alcohol ratio of water (1:1) is 25, and the GF of the graphene nonwoven fabric prepared by swelling with an alcohol ratio of water (1:4) is 9.5. The three graphene nonwoven fabrics / polyurethane composite materials with different structures all have excellent performance in multiple tensile strain cycles. The present invention provides a simple and fast structural design method for the in-depth research and application of graphene nonwoven fabrics.

[0081] Comparative Example

[0082] A method for preparing a graphene non-woven fabric / polyurethane conductive composite material, comprising:

[0083] (1) centrifuging the graphene oxide aqueous dispersion at 8000 rpm to replace water in the solution with dimethylformamide (DMF) to form a graphene oxide / DMF dispersion with a concentration of 8 g / ml;

[0084] (2) by a wet spinning method, at a pushing speed of 0.08 mm / min, the graphene oxide solution was squeezed into an ethyl acetate coagulation bath through a needle to coagulate and form, after being pulled, dried at 50° C., the fiber was stretched to a certain extent after being drawn by a guide roller, and then wound and collected at a winding speed of 1.8 rpm to prepare graphene oxide long fibers;

[0085] (3) Dry the prepared graphene oxide fiber at 30°C for 12 hours and then at 70°C for 3 hours, then put it into ethyl acetate and immediately break it into short fibers with uniform length distribution using a homogenizer at a speed of 10,000 rpm, filter it and pour it into a mixture of ethyl acetate / water solution prepared in different volume ratios, swell for 1 minute and then vacuum filter it. The graphene oxide non-woven fabric obtained after filtration is dried and reduced at high temperature to obtain a graphene fiber non-woven fabric;

[0086] (4) The prepared graphene fiber non-woven fabrics with different cross-linking degrees were cut into rectangles of 10x30 mm, copper wires were glued to both ends with conductive silver glue, and then placed in a polytetrafluoroethylene sample plate. After drying at 60°C for 10 min, the prepared TPU solution was taken out and poured into the plate. After vacuum defoaming, the plate was dried at 45°C for 10 h.

[0087] The graphene nonwoven fabric / TPU composite material obtained above was placed in a fixture, and a tensile testing machine-digital source meter combination was used to measure the resistance change of the material under ultimate tensile fracture at a speed of 12 mm / min.

[0088] In the comparative example, ethyl acetate was used to replace alcohol, and mixed with water (except alcohol, there are other more solvents that can be used, and the use of other solvents is likely to bring changes in other properties). The focus of the present invention is the swelling effect of water on graphene oxide fiber, and the addition of alcohol is mainly used to suppress swelling effect, so as long as it is a non-dispersible solution of graphene oxide, in theory, alcohol can be replaced as a swelling solution, and ethyl acetate can also be used, but the key factor is that many inhibitory solutions have bad mixing properties with water, and even many organic solvents cannot be evenly dispersed and dissolved in water, which can cause the overall swelling effect of graphene oxide film to be inhomogeneous. The result of the test shows that the effect of using other solvents (such as ethyl acetate) is not as good as the effect of using alcohol and water and alcohol to water volume ratio 4:1, 1:1, 1:4, and the effect of using alcohol water is the best.

[0089] Although several embodiments of the present invention have been given herein, those skilled in the art should understand that the embodiments of the present invention may be modified without departing from the spirit of the present invention. The above embodiments are merely exemplary and should not be used as a limitation on the scope of the present invention.

Claims

1. A method for preparing a graphene non-woven fabric / polyurethane conductive composite material, characterized in that: The preparation method comprises: S1. Preparing graphene oxide fibers by wet spinning; S2, the graphene oxide fibers obtained in step S1 are broken by homogenization, swelled by solution, and vacuum filtered to obtain a graphene oxide non-woven fabric; S3, chemically reducing the graphene oxide non-woven fabric obtained in step S2 with hydroiodic acid and performing high-temperature reduction to obtain a graphene non-woven fabric; S4, coating the graphene non-woven fabric obtained in step S3 with a polyurethane TPU solution and curing the solution to obtain a graphene non-woven fabric / polyurethane conductive composite material; In step S2, the solution is swelled, and the graphene oxide non-woven fabric is swelled using three swelling parameters of alcohol to water volume ratio of 4:1, 1:1, and 1:4; In step S3, the prepared graphene oxide non-woven fabric is reduced using hydroiodic acid / acetic acid at 90° C. for 12 hours and then at 1600° C. for 40 minutes to obtain the graphene non-woven fabric.

2. The method for preparing the graphene nonwoven fabric / polyurethane conductive composite material according to claim 1, characterized in that: In step S1, the diameter of the needle used to prepare the graphene oxide fiber is 0.13 mm, 0.18 mm or 0.25 mm.

3. The method for preparing the graphene nonwoven fabric / polyurethane conductive composite material according to claim 1, characterized in that: In step S2, the weight of the graphene oxide fiber is between 0.02-0.1 g.

4. The method for preparing the graphene nonwoven fabric / polyurethane conductive composite material according to claim 1, characterized in that: In step S4, the reduced graphene non-woven fabric is cut into widths of 0.5 cm, 1 cm, 1.5 cm or 2 cm, placed in a mold, coated with a polyurethane TPU solution, and cured.

5. The method for preparing the graphene nonwoven fabric / polyurethane conductive composite material according to claim 4, characterized in that: In step S4, when the polyurethane TPU solution is coated, the film thickness is controlled by adjusting the amount of the polyurethane TPU solution.

6. A graphene nonwoven fabric / polyurethane conductive composite material, characterized in that: The composite material is prepared using the preparation method according to any one of claims 1 to 5.

7. The graphene nonwoven fabric / polyurethane conductive composite material according to claim 6, characterized in that: Under 40% tensile strain, when the volume ratio of alcohol to water is 4:1, the GF of the graphene nonwoven fabric prepared by swelling is 100; When the volume ratio of alcohol to water is 1:1, the GF of the graphene nonwoven fabric prepared by swelling is 25; When the volume ratio of alcohol to water is 1:4, the GF of the graphene nonwoven fabric prepared by swelling is 9.

5.

8. A graphene nonwoven fabric / polyurethane strain sensor, characterized in that: The strain sensor uses the graphene non-woven fabric / polyurethane conductive composite material as described in claim 6 or 7; the preparation method of the strain sensor is: cutting the prepared graphene fiber non-woven fabric into rectangular blocks, gluing copper wires at both ends with conductive silver glue and placing it in a polytetrafluoroethylene sample plate, taking it out after drying and pouring the prepared polyurethane TPU solution, vacuum defoaming and drying, and then obtaining a graphene non-woven fabric / polyurethane strain sensor.

Citation Information

Patent Citations

  • Self-blended graphene fiber and preparation method thereof

    CN106948165A

  • Self-fused graphene oxide fiber paper and preparation method thereof

    CN109295796A